An Environmental Scan of Educational Technology Courses in Ontario Teacher Education Programs - Estaiteyeh, Mohammed; Rong, Wenting (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
In light of lessons learned from online teaching during the pandemic in 2020 and the rapid advancement of educational technologies, greater attention has been directed toward how teachers are being prepared for future classrooms. In teacher education programs, two main models exist to promote the digital competence of teacher candidates (TCs): (a) specialized, stand-alone courses on educational technology, and (b) an infused model in which digital skills are integrated into other courses. We conducted an environmental scan of educational technology courses in teacher education programs across Ontario between April and August of 2024 to explore the models adopted for preparing TCs. The findings show that 14 out of 16 Primary/Junior programs, 9 out of 12 Junior/Intermediate programs, and 9 out of 15 Intermediate/Senior programs, offer stand-alone courses on educational technology, most of which are mandatory. This reliance on stand-alone courses demonstrates an attention to technology training for TCs. However, a potential limitation lies in that most programs rely on only one course. To obtain detailed insights, we also conducted a thematic analysis of the course descriptions, highlighting areas of strength and those needing improvement. This study informs teacher education programs and researchers on future opportunities to develop TCs’ digital competence.